Kuat Tekan Beton Pasca Bakar Menggunakan Hammer Test Dan Compression Testing Machine (Ctm) - Widianto, Devit; Suryanita, Reni; Sitompul, Iskandar Romey (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Concrete is a construction material that is widely used in construction because it has many advantages. One of the advantages of concrete construction is that it is resistant to fire. However, the occurrence of a fairly high temperature change will have an impact on concrete, one of which is the change in the strength of the concrete. Therefore, this research was conducted to determine the physical change and the change of strength in post burn concrete. The concrete strength was measured with hammer test and compressive test. 18 concrete cylinder with size of 150 mm and height of 300 mm were fabricated with 3 quality variations, namely 20 MPa, 25 MPa and 30 MPa. Concrete were burned for 30 minutes with the temperatures range between 680-700 oC, and the concrete strength was calculated by using Nash’t and Agunwamba equation. The results showed that the concrete strength predicted by using Nash’t formula was 17, 18 and 21 MPa, respectively whice those predicted Bay pusing Agunwamba was 21, 23 and 26 MPa respectively.Keywords: Compressive strength, concrete after burn, Hammer Test, Compression Testing Machine (CTM).